promotion image of download ymail app
Promoted

If u r smart...?

answer this. 5 - 4y + y - 1 = -23

7 Answers

Relevance
  • Anonymous
    1 decade ago
    Favorite Answer

    * Combine like terms: 4-3y = -23

    * Solve equation:

    4-3y = -23

    -4 (on both sides of the equation) -4 = -3y = -27

    * Divide by -3 on both sides: Y = 9

    • Commenter avatarLogin to reply the answers
  • 1 decade ago

    The procedure is:

    5-4y+y-1=-23

    1y+y-1=-23

    2y-1=-23

    1y=-23

    1y over y =y

    So, the answer is y=23

    • Commenter avatarLogin to reply the answers
  • 1 decade ago

    let's see, -4y+y equals -3y, 5-1 equals 4, so now the equation reads 4-3y=-23, so you move the four to the right, making it a negative four, so it'll be -23-4 which equals -27, divided by 3y, so it'll be -3y=-27 and try to make the y by itself so divide the negative three only, so it should equal 9

    • Commenter avatarLogin to reply the answers
  • 1 decade ago

    5 - 4y + y - 1 = -23

    5 - 3y - 1 = -23

    4 - 3y = -23

    -3y = -27

    -y = -9

    y = 9

    • Commenter avatarLogin to reply the answers
  • How do you think about the answers? You can sign in to vote the answer.
  • 1 decade ago

    5-4X-21+-1-1=23

    • Commenter avatarLogin to reply the answers
  • Anonymous
    1 decade ago

    i havent done this in a long time but i think the answer is

    5 and 4/5ths

    • Commenter avatarLogin to reply the answers
  • 1 decade ago

    4 - 3y = -23

    -3y = -27

    y=9

    • Commenter avatarLogin to reply the answers
Still have questions? Get your answers by asking now.